2020
DOI: 10.1177/1558944720966713
|View full text |Cite
|
Sign up to set email alerts
|

Complete Abolition of Opioid Prescribing in an Upper Extremity Surgical Practice

Abstract: Background Prescription opioids threaten potential addiction, diversion, and death. Nonopioid regimens have demonstrated similar efficacy for select upper extremity postoperative patients. Methods After adopting a practice policy completely abolishing opioid prescriptions, data were collected on all consecutive surgical cases for the next 6 months, without exclusion. There were 800 cases, 61% male and 39% female, with a mean age of 45. Seventy patients (9%) reported already using prescription medications emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…10,11 Some have even described successfully eliminating any and all opioid prescription in their hand and upper extremity surgery practice. 33 This study has several strengths. It includes data from 14 orthopaedic surgeons from three academic institutions which each for different patient populations, which increases the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…10,11 Some have even described successfully eliminating any and all opioid prescription in their hand and upper extremity surgery practice. 33 This study has several strengths. It includes data from 14 orthopaedic surgeons from three academic institutions which each for different patient populations, which increases the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 98%
“… 8 , 23 , 31 , 32 In addition, studies have shown that patients take more opioids when they are given larger prescriptions, although for some hand procedures, many patients achieve adequate pain control without the use of any opioids. 13 , 23 , 27 , 32 , 33 Gaddis et al 23 performed a prospective randomized study of patients undergoing minor hand surgery being provided 10 or 30 opioid pills postoperatively. They observed that patients who received larger prescriptions consumed markedly more pills after surgery and were markedly more likely to still be taking opioids at the 2-week follow-up visit (15% versus 4%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, literature 59 suggests that bony procedures are associated with increased opioid consumption quantities compared with soft tissue procedures (14 vs 9 tablets, respectively). Alternatively, some hand surgeons have completely eradicated opioids from their practice with great success 60 …”
Section: Discussionmentioning
confidence: 99%
“…After 6 months and 800 cases, his practice received only four calls from patients with questions about pain alleviation. 8 The consequence of prescribing-let alone overprescribing-opioids is not trivial. In a study of insurance claims of patients not regularly using opioids before an elective hand surgery procedure, 13.5 percent were still filling opioid prescriptions 90 days after their procedure.…”
mentioning
confidence: 99%